2022
DOI: 10.55899/09734449.22/21.1e/329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type and position of branch cuttings on rooting and root morphology in Bambusa vulgaris Schrad. ex. J.C. Wendl

Abstract: An investigation was carried out to determine the effect of type and position of branch cuttings on rooting behaviour and root morphology in Bambusa vulgaris Schard. ex.J.C Wendl. using different concentrations of Indole butyric acid (IBA) harmone Maximum rooting was observed in primary (base end) cuttings treated with 1000 ppm. The propagules from single-node basal end cuttings exhibited significantly higher values for all the root and shoot parameters studied. The advantage of utilizing branch cuttings for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Vegetative propagation in bamboo is the only way to produce propagules on a large scale because the seed availability is uncertain due to its irregular flowering but less viability. The present findings (Yadav et al 2022) showed that the Indole butyric acid (IBA) hormone contributes to the effective propagation of Bambusa vulgaris branch cuttings. It is suggested that the one-node cuttings can multiply more propagules than those two and three nodes.…”
Section: Bambusa Vulgaris Schrad (Bambu Ampel)mentioning
confidence: 57%
“…Vegetative propagation in bamboo is the only way to produce propagules on a large scale because the seed availability is uncertain due to its irregular flowering but less viability. The present findings (Yadav et al 2022) showed that the Indole butyric acid (IBA) hormone contributes to the effective propagation of Bambusa vulgaris branch cuttings. It is suggested that the one-node cuttings can multiply more propagules than those two and three nodes.…”
Section: Bambusa Vulgaris Schrad (Bambu Ampel)mentioning
confidence: 57%